2008
DOI: 10.1103/physrevlett.100.037204
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Strong-Coupling Effects in a Diluted Magnetic SemiconductorGa1xFexN

Abstract: The giant Zeeman splitting of free excitons is measured in Ga(1-x)Fe(x)N. Magneto-optical and magnetization data imply the ferromagnetic sign and a reduced magnitude of the effective p-d exchange energy governing the interaction between Fe(3+) ions and holes in GaN, N_{0}beta(app)=+0.5+/-0.2 eV. This finding corroborates the recent suggestion that the strong p-d hybridization specific to nitrides and oxides leads to significant renormalization of the valence band exchange splitting.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 25 publications
10
68
0
Order By: Relevance
“…The obtained N 0 β, 0.5−1 eV, is smaller than typical ironhole exchange integrals for II-VI compounds, [75][76][77][78] but of the same order as effective exchange integrals reported for wide gap DMSs 8,9,[79][80][81][82][83] With the increasing U (Fe), t 2↑ approaches the valence band (see Fig. 2), which increases the spin splitting of the VBM, and for the U (Fe)= 4 eV the N 0 β reaches 2.0 eV .…”
Section: Sp-d Couplingmentioning
confidence: 42%
“…The obtained N 0 β, 0.5−1 eV, is smaller than typical ironhole exchange integrals for II-VI compounds, [75][76][77][78] but of the same order as effective exchange integrals reported for wide gap DMSs 8,9,[79][80][81][82][83] With the increasing U (Fe), t 2↑ approaches the valence band (see Fig. 2), which increases the spin splitting of the VBM, and for the U (Fe)= 4 eV the N 0 β reaches 2.0 eV .…”
Section: Sp-d Couplingmentioning
confidence: 42%
“…In the case of magnetically doped wurtzite (wz) GaN, exciton magnetospectroscopy [25][26][27] and magnetic circular dichroism [28] were employed to evaluate the sp-d exchange energies in films deposited by metal-organic vapor phase epitaxy (MOVPE). These methods provide the magnitude of N 0 (β − α) rather accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that a strong local potential associated with the magnetic atom can enhance the biding energy (by the so-called central cell corrections) or even produce a bound state in the gap. [22][23][24] Here, examples are Mn in ZnO and Fe in GaN, 25 which can trap a hole, despite that the corresponding donor states, Mn 2+ /Mn 3+ and Fe 3+ /Fe 4+ , respectively reside in the valence band.…”
Section: Trapping and Dopingmentioning
confidence: 99%